2021
DOI: 10.1590/2175-7860202172022
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of plant communities at edge and interior of a submontane Atlantic Forest: greater functional than compositional stability

Abstract: We compared the functional diversity of community at edge and interior areas of an Atlantic forest fragment to test the hypothesis that higher functional diversity exists along edges - in consonance with their higher abundance and floristic diversity as compared to the interior of the forest. By considering a set of vegetative, reproductive and phenological traits and ecosystem service aspects of edge and interior environments, we defined plant functional groups using Cluster Analysis, followed by a silhouette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In this sense, edge trees are often reported presenting low wood density, smaller diameters, and shorter heights compared to individuals from the interior of the forest remnant (Oliveira-Filho et al, 1997;Magnago et al, 2014;Rodrigues et al, 2016;Berenguer et al, 2018). However, some studies suggested that they do not signifi cantly diff er in functional traits concerning habitat types (Pires et al, 2014;Magnago et al, 2014;Couto-Santos et al, 2021). In context, functional traits can make it possible to infer successional ecological processes (Chazdon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, edge trees are often reported presenting low wood density, smaller diameters, and shorter heights compared to individuals from the interior of the forest remnant (Oliveira-Filho et al, 1997;Magnago et al, 2014;Rodrigues et al, 2016;Berenguer et al, 2018). However, some studies suggested that they do not signifi cantly diff er in functional traits concerning habitat types (Pires et al, 2014;Magnago et al, 2014;Couto-Santos et al, 2021). In context, functional traits can make it possible to infer successional ecological processes (Chazdon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…: Rocha and Amorim, 2012;Eisenlohr and Oliveira-Filho, 2015;Pontes et al, 2019). In this sense, edge studies usually aim at assessing functional diversity (Tabarelli et al, 2010;Magnago et al, 2014;Couto-Santos et al, 2021). When exploring the functional traits of trees, they are continuously oriented to studies in small remnants (Nascimento and Laurance, 2006;Santos et al, 2008;Santo-Silva et al, 2016), with particular species (Costa et al, 2020), and in specifi c environmental gradients (Rodrigues et al, 2016).…”
Section: Introductionmentioning
confidence: 99%